Prinsip Le Mort Saisit Le Vif dalam Peralihan HakTanah: Perlindungan Hukum bagi Pembeli terhadap Penolakan Ahli Waris - Ismail, Ismail; Sri Marniati, Felicitas; Sailellah, Sirajudin (Politica: Jurnal Hukum Tata Negara dan Politik Islam, 2025)
The principle of le mort saisit le vif provides that upon the death of a person, all rights and obligations are immediately transferred to their heirs. These include both assets and liabilities, such as the obligation to complete a land sale and purchase transaction initiated by the deceased during their lifetime. A key issue arises when heirs reject the making of a Sale and Purchase Deed (Akta Jual Beli) for a transaction conducted by the testator, raising questions about the validity of the transfer of land rights and the legal protection available to the buyer. This research applies the theory of legal protection and the theory of land registration, using a normative juridical method based on legal literature and secondary data from primary, secondary, and tertiary sources. The approaches include the Legislative Approach, Conceptual Approach, Analytical Approach, and Case Approach. Legal materials are analyzed using grammatical and systematic interpretation, supported by legal construction methods. The results show that the transfer of land rights through a Sale and Purchase Deed rejected by the heirs cannot be implemented, as maintaining land registration data requires a deed made before an authorized Land Deed Official (PPAT). To ensure legal protection, the buyer may pursue legal action against the heirs for unlawful acts, since heirs inherit not only assets but also obligations, including the duty to finalize the sale and purchase transaction. This obligation entails executing and signing the deed before a PPAT, thereby upholding the principle of le mort saisit le vif and ensuring legal certainty in land registration.